Investigation of medical identity theft in healthcare sector: its statistics, effects and way out. - Olanrewaju, Rashidah Funke; yahuza, Mukhtar; Ali, Nor'ashikin Bte (2014)
Information Technology is reaching all angles of the healthcare sector in the form of electronic diagnosis, surgery consultation and medical records. With the current trends in information and communication technology in healthcare system, such as the cloud computing and ubiquitous computing, where small computers are being embedded in almost every day object around us using both mobile devices as well as wireless connections for recording, storage and delivery of medical data, the possibly of attack on these records becomes more likely. As a result, intruders has the potential to alter, steal or destroy individual medical or health insurance records, alter computer-based prescriptions at pharmacies to life-threatening doses, or make private medical condition public. Consequently, leading to negative social and psychological effects on the affected individuals. The medical identity theft may lead to wrong diagnosis and wrong decision taken on the patient, some of which may be a life threatening cases. In addition, it cost some hospitals billions of law suits. Therefore, medical identity theft (MIDT) in healthcare needs to be investigated. In this paper, MIDT statistics is explored, it’s effects and the possible ways of solving the MIDT problem.